2014
DOI: 10.1002/cssc.201402015
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Ionomer Distribution in the Catalyst Layer of Polymer Electrolyte Membrane Fuel Cells for High Temperature Operation

Abstract: Ionomer distribution is an important design parameter for high performance polymer electrolyte membrane fuel cells (PEMFCs); however, the nano-scale modulation of the ionomer morphology has not been intensively explored. Here, we propose a new route to modulate the ionomer distribution that features the introduction of poly(ethylene glycol) (PEG) to the cathode catalyst layer and the leaching the PEG phase from the catalyst layer using a water effluent during operation. The key concept in the approach is the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…In addition to glycerol, various kinds of organic solvents in the modified decal-transfer method have been investigated to achieve the optimal solvent with high cell performance. Poly­(ethylene glycol) (PEG) has been introduced in the solvent to expand the ionomer thin film, increasing the ECSA and ionic conductivity. , In addition, PEG resulted in an increased pore size and hydrophilicity, enhancing mass transfer . Kim et al found that the use of organic solvents with higher chain mobility (NMP and dimethyl sulfoxide (DMSO)) can produce a dense catalyst layer when compared to IPA, leading to enhanced ECSA and ionic conductivity.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
“…In addition to glycerol, various kinds of organic solvents in the modified decal-transfer method have been investigated to achieve the optimal solvent with high cell performance. Poly­(ethylene glycol) (PEG) has been introduced in the solvent to expand the ionomer thin film, increasing the ECSA and ionic conductivity. , In addition, PEG resulted in an increased pore size and hydrophilicity, enhancing mass transfer . Kim et al found that the use of organic solvents with higher chain mobility (NMP and dimethyl sulfoxide (DMSO)) can produce a dense catalyst layer when compared to IPA, leading to enhanced ECSA and ionic conductivity.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
“…This last parameter is related to the ionomer interaction with the catalyst into the catalytic layer. The thermal treatment on electrodes and MEAs has a big effect on the ionomer distribution in the catalytic layer, in fact when the used temperature for the treatment is over the polymer glass transition temperature, a different arrangement of the polymeric matrix occurs leading to a high double layer capacitance (42 versus 12 mF/cm 2 ) [36] . Since the ECSA and the C dl variation are strictly related to the degradation phenomena of catalytic layer (carbon corrosion, catalyst and ionomer degradation), the values reported after AST clearly indicate the more pronounced degradation effect when T > T g is used during the thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Isopropyl alcohol (IPA) is the most commonly used solvent. Other solvents, such as glycerol [82], N-methyl-2-pyrrolicone (NMP) [83] and polyethylene glycol (PEG) [84] have been explored to increase the catalyst-water-ionomer interface. Kim et al [85] investigated the mobility of the polymeric chains in Nafion ionomer dispersion in IPA, dimethyl sulfoxide (DMSO) and NMP.…”
Section: Improving Ionomer/catalyst Interfacementioning
confidence: 99%